Modeling pressure calculations in a stress-sensitive reservoir with a multistage fractured horizontal well. Issue 6 (2nd November 2019) - Chen, Peng; Guo, Kangliang; Li, Ning; Lu, Song; Lin, Lili
ABSTRACT: Fractured horizontal wells have been widely used in tight reservoirs. The distribution of the formation pressure is related to the fracturing design, well pattern optimization and development effect. In addition, there is generally a stress sensitivity effect in tight reservoirs, which makes the pressure distribution more complex. Therefore, it is necessary to analyze the formation pressure distribution in the development process of tight reservoirs by fractured horizontal wells. In this paper, using the Pedrosa transform, perturbation transform, Green formula and boundary element method, a pressure calculation model is first built and solved for a stress-sensitive reservoir with a multistage fractured horizontal well. Second, comparing the bottom hole pressure of this method with those of existing tight reservoir models illustrates the accuracy of this model. Finally, pressure contours with different permeability moduli and boundaries are obtained by solving the seepage model. The results indicate that this model can conveniently calculate the pressure at any position in stress-sensitive reservoirs with arbitrary boundaries. The pressure contours show that the stress-sensitive effect occurs mainly near the wellbore and affects the pressure distribution of this region. The results have a certain significance for fracturing design and well pattern optimization, which is beneficial for improving the development efficiency of tight oil reservoirs.